Pengaruh Tindakan Percutaneous Coronary Intervention Terhadap Nilai Thrombin Antithrombin Complex (TAT) Pada Pasien Penyakit Jantung Koroner di RSHAM - Yugi Tri Hutomo (Jurnal Impresi Indonesia, 2025)
Percutaneous coronary intervention (PCI) is currently the most commonly used invasive procedure in patients with coronary artery disease (CAD). PCI procedure can cause friction to the endothelium leading to the release and activation of thrombin. Thrombin activation increases the risk of restenosis. This study aims to determine the effect of PCI on TAT levels in coronary artery disease (CAD) patients. This study was conducted on CAD patients who will undergo PCI and have met the inclusion criteria. Blood samples were collected before and after PCI procedure and were examined for TAT measurements. The value obtained is then analyzed based on changes in values before and after the PCI procedure, and is significant if the p-value <0.05. A total of 20 subjects, 17 males and 3 females. The mean of pre-PCI procedure for and TAT were 6.1 ± 1.02 while the mean of post-PCI procedure for TAT were 5.17 ± 1.36, with a significant with the p-value <0.001. There is an increase level of AT-III and a decrease level of TAT in post-PCI CAD patients.